2001
DOI: 10.1161/01.cir.103.5.634
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Ex Vivo Expanded Endothelial Progenitor Cells for Myocardial Ischemia

Abstract: Ex vivo expanded EPCs incorporate into foci of myocardial neovascularization and have a favorable impact on the preservation of left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
729
4
19

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,117 publications
(779 citation statements)
references
References 22 publications
27
729
4
19
Order By: Relevance
“…In terms of the functionality of differentiated CD133+ cells, the results seem to be in accordance with a pre-clinical study of Kawamoto et al [22]. In this study, the EPC differentiated in vitro infused in the ischemic area of rats with acute myocardial infarction were found (through posteuthanasia histological study) in the area of neovascularization.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of the functionality of differentiated CD133+ cells, the results seem to be in accordance with a pre-clinical study of Kawamoto et al [22]. In this study, the EPC differentiated in vitro infused in the ischemic area of rats with acute myocardial infarction were found (through posteuthanasia histological study) in the area of neovascularization.…”
Section: Discussionsupporting
confidence: 91%
“…2) Recent reports that arteriogenesis is augmented by bone marrow mononuclear cells [3][4][5] and endothelial progenitor cells suggest involvement in arteriogenesis of not only proliferation of resident cells, but also migration and proliferation of circulating stem cells/precursor cells. [6][7][8] Although previous studies have demonstrated capillary formation (vasculogenesis/angiogenesis) by transplanted cells, [7][8][9][10] they could not demonstrate incorporation of transplanted cells into pre-existing arterioles and arteries, inducing arteriogenesis. In contrast to arteriogenesis, few studies have been conducted examining venogenesis, and little is known about its mechanisms.…”
mentioning
confidence: 94%
“…Endothelial progenitor cells (EPCs) are bone-marrow derived cells that were first described in 1997 [7]. It has been hypothesised that EPCs play a role in re-endothelialisation of blood vessels damaged by ischaemia [7][8][9][10]. EPCs potentially contribute to endothelial repair by homing into sites of endothelial injury at sites of ischaemia and damage, and thus maintain the integrity of the endothelial milieu.…”
Section: Introductionmentioning
confidence: 99%